Efficacy, safety and immunogenicity of live attenuated varicella vaccine in healthy children in China: double-blind, randomized, placebo-controlled clinical trial. (August 2019) - Hao, B.; Chen, Z.; Zeng, G.; Huang, L.; Luan, C.; Xie, Z.; Chen, J.; Bao, M.; Tian, X.; Xu, B.; Wang, Y.; Wu, J.; et al.
Abstract: Objectives: To evaluate the efficacy, safety and immunogenicity of a human diploid cell SV-1 strain–based live attenuated varicella vaccine in children aged 1 to 12 years. Methods: We conducted a randomized, double-blind, placebo-controlled trial in China in which healthy children were randomly assigned in a 1:1 ratio to receive one dose of varicella vaccine or placebo. The efficacy monitoring period was 6 to 7 months for each subject. The primary endpoint was the occurrence of laboratory-confirmed varicella. Efficacy and immunity were assessed in the per-protocol cohort, and safety was assessed in the total vaccinated cohort. The file was registered withClinicalTrials.gov (NCT02981836 ). Results: Between 22 August 2016 and 19 September 2016, a total of 5997 children (2997 in the varicella vaccine group and 3000 in the placebo group) were vaccinated, and 5991 children (2995 in the varicella vaccine group and 2996 in the placebo group) were included in the per-protocol efficacy cohort. The efficacy of the vaccine was 87.1% (95% confidence interval, 69.7–94.5) against varicella (six cases vs. 46 cases) and 89.2% (95% confidence interval, 72.9–95.7) breakthrough varicella (five cases vs. 46 cases). No significant difference in solicited adverse reactions was found between the two groups. Serious advent events occurred among 0.8% (25/2998) children in the vaccine group and 0.7% (22/2999) in the placebo group. In the immunogenicity subgroup, the seroconversion rate was 97.1% (339/349) in the vaccine group. An antibody titre of 1:8 was associated with protection against varicella. Conclusions: The varicella vaccine was effective in the prevention of varicella in children.